Cenozoic temporal variation of crustal thickness in the Urumieh-Dokhtar and Alborz magmatic belts, Iran - Sepidbar, F; Karsli, O; Palin, RM; Casetta, F (Elsevier, 2021)
We present regional variations of whole-rock Sr/Y and (La/Yb)N ratios of magmatic rocks along the Cenozoic Urumieh-Dokhtar and Alborz magmatic belts, Iran. Both the magmatic belts are located at the north of the main Zagros Neo-Tethyan suture. The Urumieh-Dokhtar magmatic belt (UDMB), which trends NW-SE for 1000 km across Iran, was characterized by the intensive volcanism and plutonism, and defined the magmatic front (MF) of the Zagros orogenic belt. The Alborz magmatic belt (AMB) is situated to the north, and characterized by less intense magmatic activity. The Alborz magmatic belt was formed behind it in the rear-arc (RA) domain. A striking feature of the both magmatic belts is the transition from normal calc-alkaline arc magmatism during the Eocene–Oligocene to adakite-like calc-alkaline magmatism during the Middle to Late Miocene–Pliocene. The late-Cenozoic magmatism of the UDMB and AMB shows higher Sr/Y and (La/Yb)N. However, it should be noted that crustal thickening event is intensive in the UDMB than AMB during Late Cenozoic. Using the composition of the Lale-Zar zircons from the SE UDMB we determined the oxygen fugacity (fO2) during zircon crystallization to be between FMQ (fayalite–magnetite–quartz buffer) -0.69 to +2.41, whereas those of the Hashroud-Teckmdash-Gormolla zircons from NW AMB range from −1.22 to +5.99. The fO2 estimates suggest relatively more oxidized conditions for the Late Cenozoic igneous rocks of the AMB. Compiled data from the UDMB and AMB intrusions show an increase in average zircon crystallization temperatures with decreasing age. These outcomes have been interpreted in terms of variation of the crustal thickness, from 30 to 35 km during Eocene-Oligocene to 40–55 km during the middle-late Miocene. We propose the increase in crustal thickness is associated with the collision between the Arabian plate and Iran and subsequent convergence during the middle-late Miocene.